THE RELATIONSHIP BETWEEN BREASTFEEDING AND MATERNAL DIET DURING PREGNANCY WITH THE GROWTH AND DEVELOPMENT OF CHILDREN AGED 1-2 YEARS - Endah Kusumawati; Suhartik; Sari, Defi Kristina (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2025)
Background: The first 1000 Days of Life, spanning from pregnancy until the child is two years old, is a crucial phase for human capital quality. Fetal nutritional status relies heavily on maternal intake during pregnancy, while postnatally, breast milk serves as the primary source of nutrition. Nutritional deficiencies during gestation and suboptimal breastfeeding practices can negatively impact physical growth (stunting) and cognitive development in toddlers (aged 1-2 years). Method: This study employed an observational analytic design with a cross-sectional approach. The population consisted of mothers and children aged 1-2 years in Mojo Village, Kalitidu District, Bojonegoro Regency. A sample of 30 respondents was selected using purposive sampling. Pregnancy diet data were collected using pregnancy history questionnaires, breastfeeding data via questionnaires, growth was assessed through anthropometry (Weight-for-Age, Height-for-Age), and development was measured using the Pre-Screening Developmental Questionnaire (KPSP). Data analysis was conducted using the multiple linear regression test. Result: Statistical tests using multiple linear regression tests obtained a p-value = 0.000 < 0.05, so H0 is rejected, and H1 is accepted, which means it can be concluded that there is a relationship between breastfeeding and maternal diet during pregnancy with the growth and development of children aged 1-2 years. Conclusion: There is a positive relationship between breastfeeding and maternal diet during pregnancy with the growth and development of children aged 1-2 years. Nutritional interventions must commence during the prenatal period and continue with proper lactation management.